Current-induced rotations of molecular gears. (27th February 2019) - Lin, H H; Croy, A; Gutierrez, R; Joachim, C; Cuniberti, G
Abstract: Downsizing of devices opens the question of how to tune not only their electronic properties, but also of how to influence 'mechanical' degrees of freedom such as translational and rotational motions. Experimentally, this has been meanwhile demonstrated by manipulating individual molecules with e.g. current pulses from a Scanning Tunneling Microscope tip. Here, we propose a rotational version of the well-known Anderson-Holstein model to address the coupling between collective rotational variables and the molecular electronic system with the goal of exploring conditions for unidirectional rotation. Our approach is based on a quantum–classical description leading to effective Langevin equations for the mechanical degrees of freedom of the molecular rotor. By introducing a time-dependent gate to mimic the influence of current pulses on the molecule, we show that unidirectional rotations can be achieved by fine tuning the time-dependence of the gate as well as by changing the relative position of the potential energy surfaces involved in the rotational process.